PRACTICAL METHODS TO BOOST ENGLISH VOCABULARY (Лучшие интеллектуальные исследования, 2025)
ABSTRACT: Vocabulary acquisition is a fundamental aspect of language learning, essential for effective communication and overall language proficiency. This study investigates three practical methods for enhancing English vocabulary: spaced repetition, contextual learning, and digital tools. Using a six-month experimental design, 120 participants of varying proficiency levels were assigned to one of these methods. The results indicate that contextual learning is the most effective approach for vocabulary retention and practical application, while spaced repetition excels in memorization and digital tools offer high engagement but moderate outcomes. The findings underscore the importance of combining these methods to create a multifaceted approach that maximizes vocabulary growth. This article provides actionable insights for learners and educators, emphasizing the need for tailored, comprehensive strategies in vocabulary instruction.